Rumen Ciliated Protozoa of the Free-Living European Bison (Bison bonasus, Linnaeus) - Kišidayová, Svetlana; Durkaj, Dominik; Mihaliková, Katarína; Váradyová, Zora; Puchalska, Julia; Szumacher-Strabel, Małgorzata; Cieślak, Adam; Gizejewski, Zygmunt (Frontiers in Microbiology, 2021)
This study aims to the population analysis of the rumen ciliated protozoa of the free-living European bison (wisent, Bison bonasus, Linnaeus). The samples of the rumen fluid from the 18 bison subjected to the controlled culls within the free-ranging population in the Bialowieza primeval forest in Poland were collected and examined. The examined ciliates population consisted of the species of the families Isotrichidae and Ophryoscolecidae. There were 12 genera (Isotricha, Dasytricha, Diplodinium, Elytroplastron, Entodinium, Eodinium, Epidinium, Eremoplastron, Eudiplodinium, Metadinium, Ophryoscolex, and Ostracodinium) and 32 morphospecies of the ciliates. We observed the prevalence of a type B protozoan population (56% animals) with the typical Epidinium and Eudiplodinium genera members. Other examined animals possessed the mixed A-B population with Ophryoscolex genus, distinct for type A ciliate population. The average total ciliates count was 277 ± 103.103/ml (mean ± SD). The most abundant genera were Entodinium, 83 %, and Dasytricha, 14 %. The abundance of other genera was less than 1 % of the total count. Within the 16 Entodinium species determined, the most abundant species was E. nanellum (16.3 % of total ciliates count). The average Shannon-Wiener diversity index was 2.1 ± 0.39, evenness of 0.7 ± 0.11, and species richness of 24 ± 3.0 (mean ± SD). Our study is the first report on the population composition and diversity of rumen ciliates of E. bison. The composition and counts of ciliate genera and species were similar to the composition and counts of the rumen ciliated protozoa of American bison and many other kinds of free-living and domestic ruminants. Our E. bison ciliate population analysis has shown medium ciliate density and high diversity typical for large free-living ruminants with mixed feeding behavior.